When creativity wakes up emotions: an illustration of a creative course for pre-service teacher training - Aleksandra Vuichard; Isabelle Capron Puozzo (Springer, 2024)
Abstract In the current dynamic society, creativity stands as a crucial asset, empowering individuals to devise new and inventive solutions to navigate the shifts accompanying societal evolution. This trend significantly influences both the preparation of future educators and the ongoing professional growth of practicing teachers. It's essential to consider the connection between students' emotional experiences during the learning process to foster their creativity. The correlation between a person's emotional state and their creativity shows that both negative and positive emotions can influence creative expression. Furthermore, emotional intelligence (EI) is assumed to help prioritize thinking and manage emotions in different life situations, with the initial EI process being assessing and expressing of emotions. This study evaluates the emergence of emotions experienced by students in an academic context, focusing on action-research with Master's students (n = 10), who are future teachers for Secondary schools in Switzerland. Throughout the creative course, participants utilized a Creative Process Report Diary (CRD) to document the emotions they experienced while engaging in the diverse creative activities. The findings of this study indicate that participants predominantly encountered positive emotions during creative activities, such as enthusiasm and pleasure. Initial emotions sometimes leaned towards the negative spectrum, characterized by frustration or fear. However, as the creative activity unfolded, these emotions evolved into more positive ones, such as pleasure or interest. This study contributes to our understanding of the interplay between emotions and creativity and provides insights into how managing these emotions can foster a productive and creative learning environment for future teachers, even though emotional intelligence was not directly tested in this research.